Politics and power in the multinational corporation the role of institutions, interests and identities - Dörrenbächer, Christoph 1961-; Geppert, Mike 1964- (Cambridge University Press, 2011)
This book was first published in 2011. The current financial and economic crisis has negatively underlined the vital role of multinational companies (MNCs) in our daily lives. The breakdown and crisis of flagship MNCs, such as Enron, WorldCom, Lehman Brothers, Toyota and General Motors, does not merely reveal the problems of corporate malfeasance and market dysfunction. It also raises important questions, both for the public and the academic community, about the use and misuse of power by MNCs in the wider society, as well as the exercise of power by key actors within internationally operating firms. This book examines how issues of power and politics affect MNCs at three different levels; the macro-level, the meso-level and the micro-level. This wide-ranging analysis shows not only that power matters but also how and why it matters, pointing to the political interactions of key power holders and actors within the MNC, both managers and employees